Kenya, The Influence of Social Capital on Sustainable Agriculture in Marginal Areas, 2003 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The data for this study comes from a survey of rural households in Machakos and Taita-Taveta Districts. Four sub-locations were chosen in each district on the basis of terracing density and physical infrastructural endowments such as road network. Two sublocations with higher terracing density but with higher and lower physical infrastructural endowments were selected in each district. Likewise, two sublocations with lower terracing density but with higher and lower physical infrastructural endowments were also selected. A village was then selected randomly from each of the sub-locations. The survey through the use of a structured questionnaire then commenced in each district with about 40 households in each village, chosen randomly also. In addition to this, village profiles using focused group discussions were carried out. The overall objective of the study was to investigate, analyze, and document farm level social capital in marginal areas and evaluate its effects on soil conservation investments, resource use patterns and agricultural productivity with consequent food security implications. The specific objectives were: To study and characterize social capital. To investigate whether differential social capital influence farm level soil and water conservation investments. To investigate whether there is a link between social capital, resource use and agricultural productivity.